An Analysis Of Teacher Illocutionary Speech Acts In Teaching English At SMA 8 Pangkep - Saiful, Muhammad Yusril; Sujariati; Burhanuddin, Wildhan (FKIP Unismuh Makassar, 2023)
The purpose of this study is to identify the kinds of illocutionary utterances the teacher employs during instruction. This study's design is a qualitative one that use the descriptive approach. The dialogues that the teacher conducted while teaching and learning were the source of the research data. The research instrument was observation and recording, following which the researcher did a transcription and the researcher himself collected, processed and presented the data acquired in this study. The results demonstrate that the teacher engages in four different sorts of illocutionary acts: directive, representational, expressive, and commissive. The teacher employs 68 instances of this illocutionary behavior type. Directive was employed 32 times (47.05%), representational 16 times (23.52%), expressive 13 times (19.11), and commissive 3 times (4.41%) out of the 68 utterances. During the teaching and learning process, teachers often carry out directives. Because the use of directives in the teaching and learning process can be used to manage and control student behavior and activities. By using questioning, the teacher encourages more active participation from the class.